Kedudukan Artificial Intelligence (AI) sebagai Hak Kekayaan Intelektual dalam Perspektif Hak Cipta di Indonesia - Alfatri Anom; Lona Puspita (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2025)
Artificial Intelligence (AI) is developing as a new challenge in the regulation of copyright law in Indonesia. This certainly raises the issue of creating a legal vacuum and there is no legal certainty. “Creator” in Indonesian law implicitly limits the creation to humans, posing a fundamental challenge to recognize AI as a creator or its work as an object of copyright without human involvement. This research aims to find out how the position of AI as intellectual property rights in the perspective of copyright in Indonesia. The research employed a qualitative method with normative legal studies analyzing the secondary data that consist of primary, secondary, and tertiary legal materials. The results showed that the position of AI as an intellectual property right in the perspective of copyright in Indonesia has not been regulated in Law Number 28 of 2014 concerning Copyright.